UNCOVERING THE POWER OF WEBSITE DESIGN AND PRODUCT PHOTOS: HOW FLASH SALES PROGRAMS SHAPE PURCHASING DECISIONS - Sofyan Lazuardi; Tri Wahjoedi (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
A study was conducted to investigate how website design and product photos impact purchasing decisions, with a focus on the role of flash sale programs. The research targeted students in Surabaya who have made purchases on the Shopee e-commerce platform, with a sample size of 96 individuals. The data collected from the respondents' questionnaires were analyzed using SEM SmartPLS-3. The findings of the study revealed that flash sale programs, product photos, and website design play a crucial role in influencing consumer decisions. While flash sale programs can generate consumer interest, it is important to manage them wisely to avoid any negative impact on consumer perception. On the other hand, high-quality product photos and a well-designed website can enhance consumer engagement in the purchasing process. The practical implication of this research is that companies should prioritize flash sale programs, product photo quality, website design, and other marketing factors to influence positive purchasing decisions, develop effective marketing strategies, meet consumer needs, and strengthen their brand image. The main contribution of this study lies in the inclusion of the moderating role of flash sale programs in the integrated model of e-commerce marketing. Therefore, this research provides a deeper understanding of the factors that influence consumer purchasing decisions in the e-commerce context, while also serving as a foundation for companies to design more effective and responsive marketing strategies.